Pengaruh Kepemimpinan Terhadap Pengambilan Keputusan Strategis Dalam Bisnis - Antariksa, Nabiel Salim; Purnama, Ilham; Agustiansah, Ananda; Suandi, Zeri Fratam; Putri, Kinanti Dean Eka; Rizqinan, M Askyal (Universitas Pahlawan Tuanku Tambusai, 2024)
This article reviews the influence of leadership on strategic decision-making in business, which is strongly influenced by leadership styles. Different leadership styles can influence the decision-making process, either through the research, design, selection stages, or through the strategic, technical, and operational decision levels. Effective leadership can increase employee motivation and create a favourable environment for strategic decision-making. Leaders who provide opportunities for employees to participate in decision-making, reward and support employees who achieve targets, and provide clear direction and goals can improve the quality of decision-making. In business, good strategic decision-making is critical to achieving company goals. Therefore, effective leadership can influence the strategic decision-making process and create an environment that supports good decision-making. This research uses the literature analysis method. This approach is done by collecting information from various sources such as books, journals, and other references that are relevant to the topic we are researching. We also selected some books that discuss the topic of peer pressure and how to deal with it to support this research. transformational leadership that can improve team capabilities viz: increasing team motivation, helping the team to develop new abilities and skills, creating a positive and supportive work atmosphere, and increasing team motivation.